Consumer experiences and values in Brazilian Northeast shopping centers - Maria Raquel Lucas; Simone Maia Pimenta Martins Ayres; Nuno Rebelo dos Santos; Andreia Dionísio (Innovative Marketing)
This study aims to expand the knowledge on consumer experiences and values from an innovative marketing perspective in the context of shopping centers of inland towns in the Brazilian Northeast region. A qualitative approach was adopted using 50 in-depth interviews of shopping center visitors to collect data. Interpretative Phenomenological Analysis was used to evaluate the data. The results revealed two main categories: unpleasant and pleasant experiences. In terms of main results, 23 participants have a mix of pleasant and unpleasant experiences, while 24 report only pleasant, and 3 – unpleasant experiences. The unpleasant experiences are mostly related to the excess of people (n = 19). In what refers to pleasant experiences, functionality (n = 43), and sensory (n = 33) are the two most mentioned values, being functionality the top value to consumers regardless the purpose they have in going to the Shopping Centre. The results can be relevant inputs to design and manage Shopping Centers regarding cultural adjustment by considering consumers’ experiences and values and the importance of joining competing values behind pleasant and unpleasant experiences. The study contributes to the experiential marketing literature by highlighting the importance of cultural contexts in consumer experiences and behavior research. AcknowledgmentMaria Raquel Lucas and Andreia Dionísio are pleased to acknowledge financial support from Fundação para a Ciência e a Tecnologia (grant UIDB/04007/2020).